The Influence of Compensation, Workload against Turnover with Satisfaction as the Mediating Variable - Helena, Helena; Widigdo, Aslam Mei Nur (Journal of Sustainable Economic and Business, 2025)
Objectives:This study aims to analyze the effect of compensation and workload on Turnover with job satisfaction as a mediating variable at XYZ Bank. Methodology:The population in this study consists of 63 respondents who are permanent employees at XYZ Bank. The method used in this research is Structural Model-Partial Least Square (SEM-PLS) data analysis. The study found a significant negative effect of compensation on turnover. Finding: A significant positive effect of compensation on job satisfaction was also found. A significant negative effect of workload on turnover was found. A significant positive effect of workload on job satisfaction was found. A not significant negative effect of job satisfaction. There is a significant negative influence of compensation and workload on turnover through the job satisfaction variable. Conclusion: The conclusion obtained from this study the company can provide compensation that is aligned with employment agreements, years of service, work experience, and applicable regulations, a balance between the workload assigned to employees and their individual abilities, increase compensation in line with the intensity of the work, years of service, and work experience and enhance job satisfaction in terms of compensation and a balanced workload.